The Impact of Company Dimensions and Marketing Strategy on Tax Avoidance Practices: Empirical Study of Mining Sector Manufacturing Companies - Sugiat, Jajang (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research aims to explore the impact of company dimensions and marketing strategies on tax avoidance practices in manufacturing companies in the mining sector listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The data used in this research is panel data from manufacturing companies in the mining sector listed on the IDX during that period. Panel regression analysis is used to test the relationship between company size (SIZE) and marketing (Market) variables on tax avoidance practices (ETR). The results of the analysis show that company size has a significant influence on tax avoidance practices, although it does not reach the 5% significance level. On the other hand, marketing variables do not show a significant influence on tax avoidance practices. These results confirm previous findings that company size plays an important role in tax avoidance practices in the mining sector. Nevertheless, the implications of marketing strategies for tax avoidance should not be ignored, as this can influence a company's resource allocation and risk management. This research provides an important contribution to understanding the factors that influence tax avoidance practices in the mining sector manufacturing industry. The implications of this research can provide valuable input for the formulation of more effective policies in managing tax avoidance practices and increasing tax compliance in the sector.